Discovery of C-12 dithiocarbamate andrographolide analogue as a novel antioxidant and α-glucosidase inhibitors: In vitro and in silico studies - Utid Suriya; Chanathip Duangtha; Thanchanok Dontricharoen; Paveena Yamanont; Sakonwan Kuhaudomlarp; Prawit Thitiyanuwat; Bodee Nutho; Patcharee Arsakhant; Rungnapha Saeeng; Noppawan Phumala Morales; Supachoke Mangmool; Sutharinee Likitnukul (PLoS ONE, 2025)
Type 2 diabetes mellitus (T2DM) is a global health issue associated with oxidative stress, inflammation, and insulin resistance. Even though α-glucosidase inhibitors such as acarbose are used in treatment, their efficacy is limited by gastrointestinal side effects. In this study, we evaluated the antioxidant properties and α-glucosidase inhibition of C-12 dithiocarbamate andrographolide analogues compared to the parent compound, andrographolide. Among all analogues, compound 3f exhibited strong antioxidant activity, achieving 84% DPPH inhibition and a reducing antioxidant power activity of 254 μM ascorbic acid equivalent (AAE) at 500 μM. Additionally, molecular docking suggested a favorable binding to both yeast and human α-glucosidase at a comparable level as andrographolide, verified by the surface plasmon resonance (SPR) detection system, indicating a strong binding affinity with a dissociation constant ( K D ) of 12.86 μM. It also retains favorable physicochemical properties that align with drug-likeness based on Lipinski’s Rule. Functional assay confirmed its inhibitory activity with an IC 50 of 411 μM against the yeast α-glucosidase enzyme model, which was greater than both andrographolide and acarbose. Further molecular dynamics (MD) simulation analysis revealed that compound 3f exhibited stable and thermodynamically favorable binding to human α-glucosidase as well as interacting with key amino acids similar to those of andrographolide, providing a preliminary understanding of its potential relevance in a human enzyme context. Altogether, these findings highlight the significant potential of compound 3f as a novel α-glucosidase inhibitor, offering a potential therapeutic alternative and paving the way for further anti-diabetic drug development.